Status of elephants and poaching for ivory in Malawi: a case study in Liwonde and Kasungu National Parks - Mkanda, Francis (Pachyderm, 1993)
The post ivory trade ban period saw a drop in poaching for the commodity in Malawi. In 1991 an assessment of elephant distribution, numbers and mortality was undertaken. Elephants occupy three recognizable ranges of which two cross international boundaries. Data from Liwonde National Park show that the elephant population has remained stable since 1978. The population in Kasungu has most probably declined due to crop protection shooting and poaching.